EDUKASI DAMPAK PERNIKAHAN DINI DI DESA RIDOMANAH - Damayanti, Ema; Ash Shabah, Musyaffa Amin; Suprihatin, Suprihatin (Al-Ihsan: Journal of Community Development in Islamic Studies, 2024)
Early marriage is a marriage that is carried out by early childhood or has not reached the age allowed for marriage. In law, marriage is allowed when you reach the age of 19 years. However, there are still many people who practice early marriage, especially rural communities. Early marriage has many impacts, one of which is the failure of child growth and development or stunting. In this community service, the goal is to prevent early childhood marriage and stunting in Ridomanah village. In this activity, the subject is students of SMPN 2 Cibarusah, the implementation method is community education with socialization of the impact of early marriage. Based on the percentage of pre-test and post-test results, student knowledge has increased significantly, from 64.20% to 85.40%. This socialization activity on the impact of early marriage at SMPN 2 Cibarusah is quite effective and successful in increasing students' knowledge about the impact of early marriage.